Automatic Software Development as a Service (ASDaaS) - Benfenatki, Hind; Ferreira da Silva, C.; Benharkat, Aïcha-Nabila; Ghodous, P. (Proc. of the 4th International Conference on Cloud Computing and Services Science (CLOSER 2014), 2014)
Cloud-based services have become a norm for business application development. With Cloud Computing and the convergence toward Everything as a Service “XaaS”, we no longer consider the classical context of application development, where IT teams or integrators are solicited. Current approaches in Cloud environments are usually designed for a specific Cloud platform; moreover, they are only designed for technical users. To overcome the lack of generic and complete methodology for business application development, we propose a generic methodology called Automatic Software Development as a Service (ASDaaS) which is designed for non-technical users and promotes services reuse. In our approach, we focus on the requirement description phase. We define the requirement vocabulary based on linked data principles, and extend the Linked-USDL language to describe business stakeholder’s requirements as service functions, business constraints, user preferences and QoS parameters. Our approach is illustrated with an e-commerce example.